CCQM-K170 - electrolytic conductivity at 0.5 S m-1 and 20 S m-1 - final report - Wang, Hai; Wang, Meiling; Song, Xiaoping; Seitz, Steffen; Máriássy, Michal; Nagy, Daniel; Godínez, Jorge Uribe; Aparicio, José Luis Ortiz; Vičarová, Martina; Quino, Jose Luis Gonzales; Quispe, Jimena Patricia Torrez; Vásquez Arellán, Javier; et al. (IOP Publishing, 2025)
Main text The comparison CCQM-K170 is a subsequent key comparison of CCQM-K36.2016 and CCQM-K92. It aims to demonstrate the capabilities of the participating NMIs/DIs to measure the electrolytic conductivity of aqueous electrolyte solution in the electrolytic conductivity range around 0.5 S m-1 and 20 S m-1. The coordinating institute (NIM) prepared two potassium chloride solutions with the nominal electrolytic conductivity of 0.5 S m-1 and 20 S m-1, and verified their homogeneity and stability. Seventeen and twelve NMIs/DIs, respectively, reported their measurement results of 0.5 S m-1 and 20 S m-1 samples, respectively. The institutes used primary and secondary methods, and commercial instruments. Institutes using non-NMI CRMs as calibrants or CRMs from a participating NMI were excluded from KCRV calculation. The measurement results traceable to CRMs from the same non-participating NMI were combined into one result to be used for KCRV calculation. The results of institutes which have indicated technical problems were also excluded from KCRV calculation. The medians were agreed upon as the KCRVs for 0.5 S m-1 and 20 S m-1 solutions based on CCQM/2013-22 guidance document. Good agreement of the results was observed for the majority of participants. The results of this key comparison are considered representative for electrolytic conductivity measurement of aqueous electrolyte solution in the electrolytic conductivity range 0.15 S m-1 to 1.5 S m-1 and 5 S m-1 to 25 S m-1, respectively. This KC is intended as an updated support for the corresponding calibration and measurement capabilities (CMCs) entries in the key comparison data base of the BIPM. To reach the main text of this paper, click on Final Report. Note that this text is that which appears in Appendix B of the BIPM key comparison database https://www.bipm.org/kcdb/. The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).